2016
DOI: 10.1007/s12574-016-0296-2
|View full text |Cite
|
Sign up to set email alerts
|

Carotid atherosclerosis is associated with left ventricular diastolic function

Abstract: The present study demonstrated that decreased early diastolic mitral annular velocity relates to the parameter reflecting carotid atherosclerosis. Therefore, the presence of severe carotid atherosclerosis may affect LV diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
2
3
0
Order By: Relevance
“…Albu et al37 conducted an investigation into 96 postmenopausal women and proposed that aortic PWV was an independent predictor of LVDD (OR 2.15, 95% CI 1.39–3.31, P =0.0006), while carotid plaque score did not show correlation with LVDD after adjustment. However, some investigators reported that the presence of carotid ATS was significantly related to LVDD,3840 which was in accordance with our finding. Other studies concerning arterial stiffness were not consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Albu et al37 conducted an investigation into 96 postmenopausal women and proposed that aortic PWV was an independent predictor of LVDD (OR 2.15, 95% CI 1.39–3.31, P =0.0006), while carotid plaque score did not show correlation with LVDD after adjustment. However, some investigators reported that the presence of carotid ATS was significantly related to LVDD,3840 which was in accordance with our finding. Other studies concerning arterial stiffness were not consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Regression analysis revealed that EFT in CAH patients correlates with mitral DcT .This is in agreement with the study of Van der Meer which showed that myocardial fat has progressive and harmful effects on LV diastolic function [34]. Diastolic dysfunction has been considered as one of the first echocardiographic abnormalities to appear in patients with atherosclerotic cardiovascular disease with a high rate of release of free fatty acids (FFA) [35], which encounter no physical barrier or fascia before reaching the cardiomyocytes; [36] therefore, the myocardium receives a double dose of FFA from both the EFT and the systemic circulation. EFT is a source of several bioactive molecules that might directly influence the myocardium [37].…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 85%
“…This is in agreement with the study of Van der Meer (34) which showed that myocardial fat has progressive and harmful effects on LV diastolic function. Diastolic dysfunction has been considered as one of the first echocardiographic abnormalities to appear in patients with atherosclerotic cardiovascular disease with a high rate of release of FFA (35), which encounter no physical barrier or fascia before reaching the cardiomyocytes (36). Therefore, the myocardium receives a double dose of FFA from both the epicardial fat and the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%